Histomolecular characterization of intracranial meningiomas developed in patients exposed to high-dose cyproterone acetate: an antiandrogen treatment. Issue 1 (28th May 2019) - Portet, Sylvain; Naoufal, Rania; Tachon, Gaëlle; Simonneau, Adrien; Chalant, Anaïs; Naar, Amir; Milin, Serge; Bataille, Benoit; Karayan-Tapon, Lucie
Abstract: Background: Meningiomas are the most common primary intracranial tumors in adults. The relationship between meningiomas and exogenous sex hormones such as cyproterone acetate (CPA) is well documented, yet the underlying mechanisms remain unknown. Defining the histomolecular status of meningiomas developed on CPA would help us to better understand the oncogenesis of these tumors. Methods: We identified 30 patients operated for a meningioma after long-term high-dose CPA therapy and with a history of CPA discontinuation before establishing the indication for surgical intervention. We used array-comparative genomic hybridization (to characterize copy number changes in those 30 meningiomas and subsequently performed next-generation sequencing with the National Institute of Cancer (INCa) solid tumor panel, which is a targeted panel of clinically actionable genes. We also examined grade, type, and clinical features. Results: We identified AKT1 mutations or PIK3CA mutations in 33.3% of CPA meningiomas. AKT1 and PIK3CA mutations were mutually exclusive. Enrichment in oncogenic PIK3CA mutations in the CPA cohort was detected. CPA meningiomas showed chromosomal stability and were located mainly in the skull base. Ninety percent of CPA meningiomas were low-grade meningiomas and 63.4% were meningotheliomas. Half of our CPA cohort had microcystic components. Conclusion: Our study shows that low-grade meningothelial meningiomas of the skull base are predominant in CPA meningiomas. We identified PIK3CA/AKT1 pathway as a hypothetical actor in onco-pharmacological interaction between meningiomas and CPA. This signaling pathway could be an interesting target for precision medicine trials in meningioma patients who have been subjected to CPA. Our results could invite the scientific community to review the current classification of meningiomas and to evolve toward more specific histomolecular classification.